HOMA-Adiponectin Closely Associates with Cardiometabolic Risk Markers in Middle-Aged Indians with Metabolic Syndrome - Banerjee, Joyita; Dhas, Yogita; Mishra, Neetu (Experimental and Clinical Endocrinology & Diabetes, 2020)
Background Unhealthy dietary habits and sedentary lifestyles have raised alarming concerns for the rising prevalence of metabolic syndrome (MetS) and associated cardiometabolic risk among Indians at an early age. Insulin resistance and adiposity are the important risk factors associated with MetS. The present study aimed to investigate the relationship between a modified marker of insulin resistance (homeostatic model assessment-adiponectin (HOMA-AD)) and cardiometabolic risk among middle-aged Indians.Methods The study comprised of 144 subjects of age-group 31–50 years, where 83 subjects were diagnosed for MetS according to the guidelines given by the International Diabetes Federation. We measured cardiometabolic risk indicators such as fasting blood glucose (FPG), fasting plasma insulin (FPI), homeostatic model assessment- insulin resistance (HOMA-IR), adiponectin, high sensitivity C-reactive protein (hs-CRP), oxidized LDL (oxLDL), monocyte chemoattractant protein-1 (MCP-1), and atherogenic index, among others. We calculated HOMA-AD by the formula: [FPG (mmol/l) × FPI (µIU/ml)] / [22.5 × Adiponectin (µg/ml)].Results HOMA-IR and HOMA-AD were highly increased (p<0.001) in the MetS subjects than controls. Adiponectin was significantly (p<0.01) lower whereas cardiac risk markers such as atherogenic index, hs-CRP, oxLDL, and MCP-1 were significantly (p<0.01) elevated in MetS group than controls. Linear regression showed positive and significant associations (p<0.01) of HOMA-AD with all the cardiometabolic risk markers except MCP-1. HOMA-AD showed higher AUC (0.806) than HOMA-IR (0.791) for predicting MetS.Conclusion HOMA-AD could be a surrogate adipokine-based marker correlated significantly with components of MetS and cardiometabolic risk indicators. It appeared to be a better predictor of MetS among middle-aged Indians than HOMA-IR.
Keywords: adiponectin; cardiometabolic risk; HOMA-AD; insulin resistance; metabolic syndrome; middle-aged